(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Background: Medicinal plants are an essential source of human health, therefore many studies have focused to use alternative medicine for its preventive and therapeutic importance and its benefits in others fields. Vitex agnus-castus is well known plant as herb women, because it has ability to curing many women hormone’s disorders. Objective: The present study aimed to determine aqueous extract of the leaves of Vitex agnus-castus on some of the functions and qualities of the ovaries in female white rabbit’s eggs. Methodology : Female white rabbits aged 6-8 months and weight (1300-1700) grams exposed to influence of hydrogen peroxide (0.5%) for (30) days and were rabbits age (6-8 months) and weights (1300-1700) grams, which divided randomly to 4 groups as (7) rabbits per group, as follows: a control group consumed drinking water and standard food, infected control group which consumed (H2O2) with drinking water and food, an extract group with concentration (50 mg / kg of body weight) and extract group with concentration (50 mg / kg) + H2O2. Results: ovaries showed presence a small number of primary and secondary follicles and loss mature egg follicles as well as looks like a bag inside the follicle , whilst study group that treated with aqueous extract of Vitex agnus-castus alone as well as Vitex agnus-castus group with peroxide that showed containing number of ovarian follicles in various stages of growth. Conclude: aqueous extracts of Vitex agnus-castus dose (50 mg / kg) as an antioxidant effect which showed a significant role in repairing the damage occurring in the ovary.